Effect of Boundary Conditions and Angles on the Compressive Performance of the Corner Element - Bing Xu; Lang Wang; Qin Liu; Rui Wang; Bo Xu; Bing Kong; Dan Zhang (Buildings)
The corner element is the most basic constitutive element of multi-cellular thin-walled structures; however, scenarios for using relevant theories are limited. To improve this situation, this research investigated the effect of boundary conditions on the compression performance of corner elements with different angles. The deformation laws of corner elements were also explored. The approach was based on experiments and the finite element method. The result shows the outwardly extending plates on both sides yield first, the central twisted wire region then destabilizes and exits the working state, and the plate enters the post-buckling phase. A more relaxed boundary and larger angle can make it easier for the corner elements to trigger the symmetric deformation mode. Moreover, a mechanical model for simplified computation is proposed to predict the initial peak crushing force. The research can provide a reference for studying the compression performance of energy-absorbing elements in engineering.